Design of 2-Aminobenzothiazole Derivatives Targeting Trypanosomatid PTR1 by a Multidisciplinary Fragment Hybridization Approach. - Panecka-Hofman, J.; Linciano, P.; Pohner, I.; Dyguda-Kazimierowicz, E.; Jedwabny, W.; Landi, G.; Santarem, N.; Witt, G.; Ellinger, B.; Kuzikov, M.; Luciani, R.; Ferrari, S.; et al. (J Med Chem, 2025)
Pteridine reductase 1 (PTR1) is a folate pathway enzyme essential for pathogenic trypanosomatids and a promising drug target for diseases such as sleeping sickness and leishmaniasis. Previous studies have shown that the 2-aminobenzothiazole moiety targets the PTR1 biopterin pocket, while 3,4-dichlorophenyl-containing compounds, such as I bind a different region of the Trypanosoma brucei PTR1 (TbPTR1) pocket. This study combines both moieties via various linkers, creating two compound series screened in silico against TbPTR1 and Leishmania major PTR1 (LmPTR1). In the first series, five compounds were synthesized, and 1a and 1b emerged as potent TbPTR1 inhibitors, with 1b also being active against LmPTR1 and moderately effective against Leishmania infantum. Furthermore, structure-activity relationship analysis, supported by quantum calculations and crystallography, revealed meta-halogenation to be more favorable than para, although single halogenation reduced antiparasite effects. Our fragment hybridization approach led to less toxic, more effective compounds than I.
Keywords: Structure-Activity Relationship; *Trypanosoma brucei brucei/enzymology/drug effects; *Drug Design; *Benzothiazoles/pharmacology/chemistry/chemical synthesis; Leishmania major/drug effects/enzymology; *Oxidoreductases/antagonists & inhibitors/metabolism/chemistry; *Protozoan Proteins/antagonists & inhibitors/metabolism; Leishmania infantum/drug effects/enzymology; *Enzyme Inhibitors/pharmacology/chemistry/chemical synthesis; Parasitic Sensitivity Tests; *Trypanocidal Agents/pharmacology/chemistry/chemical synthesis

The discovery of aryl-2-nitroethyl triamino pyrimidines as anti-Trypanosoma brucei agents - Linciano, Pasquale; Pozzi, Cecilia; Tassone, Giusy; Landi, Giacomo; Mangani, Stefano; Santucci, Matteo; Luciani, Rosaria; Ferrari, Stefania; Santarem, Nuno; Tagliazucchi, Lorenzo; Cordeiro-da-Silva, Anabela; Tonelli, Michele; et al. (European Journal of Medicinal Chemistry, 2024)

High-Throughput Phenotypic Screening and Machine Learning Methods Enabled the Selection of Broad-Spectrum Low-Toxicity Antitrypanosomatidic Agents - Linciano, Pasquale; Quotadamo, Antonio; Luciani, Rosaria; Santucci, Matteo; Zorn, Kimberley M.; Foil, Daniel H.; Lane, Thomas R.; Cordeiro-da-Silva, Anabela; Santarem, Nuno; B Moraes, Carolina; Freitas-Junior, Lucio; Wittig, Ulrike; et al. (Journal of Medicinal Chemistry, 2023)